Nanchang General Hospital and Social Changes in Modern Jiangxi (1897–1937) - FENG, Huiping (Journal of Research for Christianity in China (JRCC), 2024)
Mission hospitals are important medical institutions established by modern Christianity to promote medical missionary work. Since modern times, The Methodist Episcopal Mission has established multiple mission hospitals in China, which have had various impacts on the regional society of modern China. Nanchang Hospital is an important medical institution founded by American Methodist Episcopal Mission in Jiangxi. It’s earliest founding time can be traced back to 1897. After about 40 years of development, the hospital has become a large-scale comprehensive mission hospital in Jiangxi Province before the Second Sino-Japanese War in 1937. From the perspective of development history and local social relations, Nanchang Hospital and other mission hospitals have both similarities and their own unique features. Under the trend of localizing mission hospitals, Nanchang Hospital has also followed the trend and gradually localized. The interaction between the hospital and local society objectively promoted the changes in local society in Jiangxi, and had a profound impact on the medical and health care, customs, charitable relief, and foreign relations of modern Jiangxi.